Functional Expression of Transient Receptor Potential and Piezo1 Channels in Cultured Interstitial Cells of Human-Bladder Lamina Propria - Zhao, MengMeng; Chen, Zhenghao; Liu, Lei; Ding, Ning; Wen, Jiliang; Liu, Jiaxin; Wang, WenZhen; Ge, Nan; Zu, Shulu; Song, Wei; Chen, Guoqing; Zhang, Xiulin (Frontiers in Physiology, 2022)
The interstitial cells in bladder lamina propria (LP-ICs) are believed to be involved in sensing/afferent signaling in bladder mucosa. Transient receptor potential (TRP) cation channels act as mechano- or chemo-sensors and may underlie some of the sensing function of bladder LP-ICs. We aimed to investigate the molecular and functional expression of TRP channels implicated in bladder sensory function and Piezo1/Piezo2 channels in cultured LP-ICs of the human bladder. Bladder tissues were obtained from patients undergoing cystectomy. LP-ICs were isolated and cultured, and used for real-time reverse transcription-quantitative polymerase chain reaction, immunocytochemistry, and calcium-imaging experiments. At the mRNA level, TRPA1, TRPV2, and Piezo1 were expressed most abundantly. Immunocytochemical staining showed protein expression of TRPA1, TRPV1, TRPV2, TRPV4, TRPM8, as well as Piezo1 and Piezo2. Calcium imaging using channel agonists/antagonists provided evidence for functional expression of TRPA1, TRPV2, TRPV4, Piezo1, but not of TRPV1 or TRPM8. Activation of these channels with their agonist resulted in release of adenosine triphosphate (ATP) from LP-ICs. Inhibition of TRPV2, TRPV4 and Piezo1 blocked the stretch induced intracellular Ca2+ increase. Whereas inhibition of TRPA1 blocked H2O2 evoked response in LP-ICs. Our results suggest LP-ICs of the bladder can perceive stretch or chemical stimuli via activation of TRPV2, TRPV4, Piezo1 and TRPA1 channels. LP-ICs may work together with urothelial cells for perception and transduction of mechanical or chemical signals in human-bladder mucosa.